Feasibility of challenging treadmill speed-dependent gait and perturbation-induced balance training in chronic stroke patients with low ambulation ability: a randomized controlled trial - Hu, Jia; Jin, Lingjing; Wang, Yubing; Shen, Xia (Frontiers in Neurology, 2023)
Background Treadmill training shows advantages in the specificity, amount, and intensity of gait and balance practice for the rehabilitation of stroke patients. Objective To investigate the feasibility and effectiveness of challenging treadmill speed-dependent gait and perturbation-induced balance training in chronic stroke patients with low ambulation ability. Methods For this randomized controlled trial (Chinese Clinical Trials.gov registration number ChiCTR-IOR-16009536) with blinded testers, we recruited 33 ambulatory stroke participants with restricted community ambulation capacity and randomly assigned them into two groups: the experimental group with 2 week treadmill speed-dependent gait training combined with 2 week treadmill perturbation-induced balance training (EXP) or the control group with traditional gait and balance training (CON). Various variables were recorded during EXP training, including the rating of perceived exertion, heart rate, causes of pauses, treadmill speed, and perturbation intensity. Outcome measures were examined before training and at 2 and 4 weeks after training. They included gait velocity during five-meter walk test at comfortable and fast speed and reactive balance ability in the compensatory stepping test as primary outcome measures, as well as dynamic balance ability (timed up-and-go test and 5 times sit-to-stand test) and balance confidence as secondary outcome measures. Results All participants completed the study. The treadmill speed and perturbation intensity significantly increased across training sessions in the EXP group, and no adverse effects occurred. The normal and fast gait velocities showed significant time and group interaction effects. They significantly increased after 2 and 4 weeks of training in the EXP group (p < 0.05) but not in the CON group (p > 0.05). Likewise, dynamic balance ability measured using the timed up-and-go test at a fast speed significantly improved after 2 and 4 weeks of training in the EXP group (p < 0.05) but not in the CON group (p > 0.05), although without a significant time and group interaction effect. Surprisingly, the reactive balance ability did not show improvement after treatment in the EXP group (p > 0.05). Conclusion Challenging treadmill speed-dependent gait and treadmill perturbation-induced balance training is feasible and effective to improve ambulation function in chronic stroke patients with low ambulation ability.